Governance Indicators and Smart City: Transparency and Interaction a case study from the city of Belo Horizonte (Research, Society and Development, 2021)
This work sought to understand the evolution of the Municipality of Belo Horizonte through a Governance evaluation, which encompasses transparency towards citizens and the actions proposed by the municipality, emphasizing Integration, Transparency and Effective Indicators in the provision of data to identify whether the city of Belo Horizonte is a smart city. The methodology used is based on a survey of data made available on the evolution of the city of Belo Horizonte in the Connected Smart Cities ranking in 2019 and 2020; semi-structured interview with the management involved in making open data available to the population and the analysis of the evolution and effects of transparency actions in the city of Belo Horizonte as Smart City. The data were qualitatively analyzed, and as a result it is possible to point out that (1) the implementation of a Smart City undergoes several changes, evolutions and debates that dialogue with the different participating actors, (2) the public administration is the main inducer and transforming agent of this process, guided by indicators and rankings that dialogue with the city, (3) it is possible to confront the concepts found in the literature that permeate broad topics such as: elements of population growth , digital revolution, integration, diffusion, collaborative society, connectivity, transparency and governance.